2022
DOI: 10.1007/s40615-022-01387-3
|View full text |Cite
|
Sign up to set email alerts
|

Missing Race and Ethnicity Data among COVID-19 Cases in Massachusetts

Abstract: Infectious disease surveillance frequently lacks complete information on race and ethnicity, making it difficult to identify health inequities. Greater awareness of this issue has occurred due to the COVID-19 pandemic, during which inequities in cases, hospitalizations, and deaths were reported but with evidence of substantial missing demographic details. Although the problem of missing race and ethnicity data in COVID-19 cases has been well documented, neither its spatiotemporal variation nor its particular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Prior research has shown that differences in the ordering and question format for race and ethnicity data can result in inconsistent answers. 40 , 41 Misclassifications at the outset would propagate into the multiple imputation procedure. We attempted to mitigate this through our data-cleaning process, which was informed by discussions with Holyoke testing sites about how race and ethnicity data were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that differences in the ordering and question format for race and ethnicity data can result in inconsistent answers. 40 , 41 Misclassifications at the outset would propagate into the multiple imputation procedure. We attempted to mitigate this through our data-cleaning process, which was informed by discussions with Holyoke testing sites about how race and ethnicity data were collected.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 An important example of this in public health research was the finding that missing race data in COVID cases reported in Massachusetts did not occur randomly among all races and was most notable among minority races. 13 These findings of inequities in the time to treatment of syphilis along racial lines demands further investigation into contributory factors. We identified overall high treatment adequacy for early syphilis, however, 68 cases of early syphilis lacked treatment documentation or had inadequate treatment and may represent opportunities for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In large surveys, it has been demonstrated that underrepresented minorities such as African Americans, Latinx, and Asian/Pacific Islanders are less likely to report their race than White survey respondents 11,12 . An important example of this in public health research was the finding that missing race data in COVID cases reported in Massachusetts did not occur randomly among all races and was most notable among minority races 13 . These findings of inequities in the time to treatment of syphilis along racial lines demands further investigation into contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was no standardized method of collecting race or ethnicity information at testing facilities. Prior research has shown that differences in the ordering and question format for race and ethnicity data can result in inconsistent answers [39,40].…”
Section: Discussionmentioning
confidence: 99%